IMPROVING STUDENT’S READING COMPREHENSION THROUGH PICTURE IN THINK, PREDICT, READ, AND CONNECT (TPRC) STRATEGY - Isnaeni, Putri Imasari; Suparman, Ujang; Yufrizal, Hery (Universitas PGRI Sumatera Barat, 2025)
The aim of this study is to ascertain whether the reading comprehension levels of students who are taught the original TPRC strategy and those who are taught using picture in TPRC strategy differ noticeably. This study used a true-experimental design. It happened during the first semester of the second grade at SMP Islam 1 Kalirejo. A control group and an experimental group were used by the researcher. While the experimental group incorporated picture to the TPRC strategy, the control group employed the original TPRC strategy. According to the findings of the independent group t-test, the experimental and control groups' reading comprehension scores differed statistically significantly, with the significance level for both classes being less than 0.05. The mean score of the experimental group was higher (77.80) than that of the control group (68.42). These findings suggest that incorporating picture in TPRC strategy can effectively improve students’ reading comprehension. In addition, it is suggested that teachers should actively monitor student’s interactions and implement strategies to ensure all students are equally engaged.